Analisis Putusan Mahkamah Agung RI Nomor 1683 K/Pdt.Sus-PHI/2022 Terkait Pekerja PKWT Berdasarkan Undang-Undang No. 13 Tahun 2003 dan Undang-Undang Nomor 11 Tahun 2020 - Wasito, Wasito; Widagdo , Gatot S. (PT Elaborium Elevasi Indonesia, 2025)
This paper analyzes the decision of the Supreme Court of the Republic of Indonesia Number 1683 K/Pdt.Sus-PHI/2022 regarding the status of workers with fixed-term employment agreements (PKWT) from the perspective of employment law. This analysis examines how the decision is applied to the provisions of Law Number 13 of 2003 concerning Manpower and the amendments stipulated in Law Number 11 of 2020 concerning Job Creation. This case focuses on workers who have worked for a long duration with PKWT without any legal termination, which gives rise to disputes regarding the status of a permanent employment relationship. In the decision, the Supreme Court upheld the previous decision requiring companies to recognize workers as permanent workers, because the duration of the PKWT exceeded the regulated time limit. This study shows that although the Job Creation Law provides flexibility in the duration of PKWT, the protection of workers' rights must still be prioritized, and companies are required to comply with legal procedures related to employment relationships. The results of this analysis are expected to provide insight into the implementation of employment regulations in Indonesia and the legal implications of changes to the law on employment practices.